PENGARUH PEMBERIAN KOMPENSASI DAN MOTIVASI KERJA TERHADAP SEMANGAT KERJA KARYAWAN (STUDI PEGAWAI BAGIAN UMUM RSUD ARIFIN ACHMAD PROVINSI RIAU) - Syafitri, Febria; ", Suryalena (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study aims to determine the effect of providing compensation and work motivation on employee morale partially and simultaneously. This study used a questionnaire as a data collection tool that was distributed to 49 respondents to the employees of the General Section of Arifin Achmad Hospital in Riau Province. Data from the questionnaire were then processed using descriptive analysis and statistical analysis using SPSS version 2003 by conducting validity tests, reliability tests, simple linear analysis, multiple linear analysis, analysis of determination (R2) and hypothesis testing by testing t test (partial) and F test (simultaneous).The results showed that the results of testing the first hypothesis were giving compensation to employee morale, t count (5,284)> t table (2,011), meaning that the compensation variable had a significant effect on employee morale. The second incentive for employee morale is t count (8,233)> t table (2,011), meaning that giving incentives influences employee morale. The results of the F test count (46.405)> F table (3.17), meaning that compensation and work motivation simultaneously have a significant effect on employee performance. Keywords: Giving Compensation, Work Motivation, Employee Work Spirit.